Kajian Fenomenologi atas Al-‘Afwu dalam Tafsir Kontemporer dan Relevansinya Dengan Trust Issue - Hamidah, Nurul; Jamal, Khairunnas; Khotimah, Khotimah; Syaifullah, Ahmad (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This article discusses a Phenomenological Study of Al-‘Afwu in Contemporary Qur’anic Exegesis and its Relevance to Trust Issues. This research is motivated by the phenomenon that modern-era society is starting to forget the true meaning and nature of forgiveness. That's why the problem of forgiveness (Al-‘Afwu) is underestimated, so it is very easy to forgive someone but still hold a grudge against that person, resulting in many people being hit by a crisis of trust (Trust Issues). The Trust Issues here is not human belief in God, but rather the belief that arises as a result of interacting with other humans. This research focuses on discussing the relationship between Al- ‘Afwu and the Trust Issues phenomenon. This type of research is library research using a qualitative descriptive approach, namely reading and analyzing study objects related to research. The study object in question comes from primary data and secondary data. The primary source for this research is contemporary Qur’anic Exegesis books while the secondary sources come from books, journals, articles and other written sources related to the research. The research results show that without Al-‘Afwu, Trust Issue sufferers will have difficulty trusting other people again, making it difficult for themselves because humans cannot be separated from other humans. There are many ways and methods for healing Trust Issues, but if the sufferer has not forgiven themselves and the people who have hurt them, it will be in vain. That is why Allah Swt. commands his servants to have a totally forgiving nature (Al-‘Afwu), namely forgiving others and erasing mistakes that have been made by the person who hurt them without any intention of revenge so that the ties of friendship are maintained and remain harmonious.